Children's 1000 pictures to talk about: revised edition - Zaidi, Syeda Asma (Oxford University Press Karachi, 2006)
"Children's 1000 Pictures to Talk About" is an interactive picture book designed to stimulate conversation and vocabulary development in young learners. Featuring a diverse array of colorful images across various themes$1 (Bsuch as animals, nature, and everyday objects$1 (Bthe book encourages children to explore and discuss what they see.s